The Terms Mahīdh and `azā in the Interpretation of Menstruation: A Maqāshid al-Shari’ah Analysis of Surah al-Baqarah (2: 222) - Esya Heryana; Sinta Hardiyanti Utami (Yinyang: Jurnal Studi Islam, Gender dan Anak)
This study examines the meaning of mahīḍ and `azā in Surah al-Baqarah (2:222) as terms associated with menstruation. It applies a maqāshid analysis to find out the meaning behind i'tizal command and its benefits for both men and women.  These terms have often been used to justify the perpetuation of patriarchal values. The study adopts a descriptive-analytical approach, drawing on classical and contemporary exegetical perspectives, including those of Muslim feminists, while also integrating a maqāshid al-sharī‘ah framework to uncover the intended wisdom behind Surah al-Baqarah (2:222). The study reveals that interpreting the term mahidh —as referring separately to time, location, or the menstrual process itself—has allowed space for the understanding of iʿtizāl fī al-mahidh as a general injunction to avoid women during menstruation. However, a more accurate exegetical reading indicates that the verse refers specifically to abstaining from sexual intercourse, understood as avoiding the site of menstruation. This restriction serves both as an expression of respect for women and as a form of regulation over reproductive health. Furthermore, the term `azā, when interpreted solely through a textual or literal lens—as filth, impurity, blood, or something objectionable—has contributed to social and religious exclusion of women during menstruation. In contrast, a contextual reading of `azā reframes it as a unique biological condition that involves physical and psychological distress. Under such circumstances, it is more appropriate to provide women with comfort, dignity, and recognition of their reproductive rights. Consequently, the objectives of Islamic law (maqāshid al-sharī‘ah), particularly the protection of religion (hifz al-dīn), life (hifz al-nafs), and progeny (hifz al-nasl), become more apparent when this verse is approached not solely through textualist readings, but also through contextual and purposive interpretation. A maqāshid-based analysis thus carries important implications for the physical and psychological well-being of women, and shapes the discourse on sexual ethics, gender relations, and spiritual agency of women in both private and public spheres.